2010
DOI: 10.1071/cp10020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high temperature on pollen germination and spikelet sterility in rice: comparison between basmati and non-basmati varieties

Abstract: Increased temperature due to global warming may reduce pollen germination and induce spikelet sterility in rice crops. Anthesis is the most sensitive stage in rice and exposure to high temperature during this period may cause reduction in floral reproduction. Increased temperature will have different effects on different rice varieties. In the present study the effect of high temperature on pollen as well as on spikelet sterility in basmati (aromatic) and non-basmati (non-aromatic) rice varieties was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…The percent of fertile spikelets gradually declines when daily mean temperature exceed 29°C [ 50 ] or 29.6°C [ 51 ]. Chakrabarti et al [ 52 ] reported that pollen sterility gradually increased above 33°C. In spite of prevailing normal temperature one week before and after of flowering (data not shown) and normal appearance of spikelets, the number of filled grain as a percentage declined rapidly in studied hybrid varieties than in inbred BRRI dhan45 at delayed planting.…”
Section: Discussionmentioning
confidence: 99%
“…The percent of fertile spikelets gradually declines when daily mean temperature exceed 29°C [ 50 ] or 29.6°C [ 51 ]. Chakrabarti et al [ 52 ] reported that pollen sterility gradually increased above 33°C. In spite of prevailing normal temperature one week before and after of flowering (data not shown) and normal appearance of spikelets, the number of filled grain as a percentage declined rapidly in studied hybrid varieties than in inbred BRRI dhan45 at delayed planting.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, multiple abnormalities were detected in pollen tubes of the heat-sensitive genotype LGG 460, where the emergence of multiple tubes, and their bursting and coiling were observed; eventually, the pollen failed to germinate at temperatures exceeding 40°C ( Figure 10 ). Earlier reports on rice have also indicated that an increase in temperature could limit yield by affecting pollen germination and grain formation (Endo et al, 2009; Wassmann et al, 2009; Chakrabarti et al, 2010). The male gametophyte is particularly sensitive to HTs at all stages of development, while the pistil and the female gametophyte are considered to be more tolerant (Hedhly, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…indica bajo condiciones de alta temperatura. En este sentido Chakrabarti et al (2010) evaluaron el efecto de alta temperatura (28-34 ºC) sobre la viabilidad del polen de diferentes variedades de arroz de la subsp. indica y observaron que el aumento de temperatura incrementó la esterilidad del polen y redujo la germinación de los granos sobre el estigma.…”
Section: Discussionunclassified